Surface and morphology structure evolution of metal phosphide for designing overall water splitting electrocatalyst - Wang, Zuohui; Heng, Nannan; Wang, Xiaobing; He, Jinling; Zhao, Yong (Journal of catalysis, 2019)
Single and binary heterostructure metal phosphides catalysts are designed, which illustrate the importance of the catalyst structure reconstruction and subsequent deviation of its reactivity, which provide an advancement for rationally designing high performance electrocatalysts, photocatalysts, and thermal catalysts. [Display omitted] •The surface and morphology reconstruction of catalyst during catalytic process.•Binary heterostructure metal phosphides catalysts.•Core-shell structure electrocatalysts with high performance. The original active site units and morphologies structure on catalyst surface is highly important to promote the rate of chemical reaction, while less concern is paid on their dynamic change during reaction process. Understanding these reconstructions in reactions is essential to illustrate the correlations between the structure and reactivity of catalyst, as well as the rational design of efficient catalyst. Here, single metal phophide materials are adopted as model electrocatalysts to show the structure evolution in the process of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). After both OER and HER operation, the core-shell structured metal-hydroxide/oxyhydroxide@metal-phosphide catalysts are generated, resulting in the high but decreased activity. To overcome the activity deterioration of metal phosphide induced by morphology reconstruction, binary heterostructure metal phosphides catalysts are designed and show the better OER and HER activity and stability compared to those of single phosphides. The work illustrates the structure-performance relationship of catalyst surface dynamics on catalytic performance, which will provide the guidance for designing high performance electrocatalysts, photocatalysts, and thermal catalysts.